Offshore enrolment in higher education and migration: some evidence from Australia - Levatino, A (International Migration Institute, 2014)
This paper presents empirical evidence on the relationship between enrolment in transnational higher education (TNE) and subsequent skilled migration to the country that provided the educational services. Based on macro-level panel data, the analysis shows a close link between offshore enrolment in Australian higher education and subsequent skilled migration to Australia, suggesting that countries may successful use the provision of higher education outside their borders to enlarge skilled migrant recruitment. Although further research on the issue is needed, this paper represents the first step in the exploration of an issue of particular interest for both developed and developing countries, constituting an original contribution to the current debate on skilled migration, student mobility, and new trends in the higher education sector.